2012
DOI: 10.2131/jts.37.723
|View full text |Cite
|
Sign up to set email alerts
|

Predictive genomic biomarkers for drug-induced nephrotoxicity in mice

Abstract: -The present study aimed to establish candidate biomarker genes for the early detection of nephrotoxicity in mice, with a particular focus on nephrotoxicity caused by polyene macrolides. Comprehensive gene expression changes were evaluated using microarrays in a mouse model in which acute nephrotoxicity was induced by amphotericin B deoxycholate, trade name Fungizone. The upregulated genes identified through microarray analysis of kidney tissue of Fungizone-treated mice included several genes that have been re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…In addition, we observed a decrease in the expression of antiapoptotic genes, such as BCL2L1. These results are consistent with those obtained in other studies, which reinforces the role of such genes in the identification of early nephrotoxicity …”
Section: Discussionsupporting
confidence: 93%
“…In addition, we observed a decrease in the expression of antiapoptotic genes, such as BCL2L1. These results are consistent with those obtained in other studies, which reinforces the role of such genes in the identification of early nephrotoxicity …”
Section: Discussionsupporting
confidence: 93%
“…In this setting, early knowledge of ongoing AKI may enable the physician to take measures to avoid additional damage before the progression to full-blown acute tubular necrosis. Preliminary studies in rodents have shown that NGAL is a promising biomarker of AKI secondary to cisplatin (26,27), amphotericin B (AmB) (28), colistin (29), and gentamicin (30) treatment, but few studies have explored this application in humans. In 12 patients with cancer receiving cisplatin infusions, the urinary NGAL (UrNGAL) level rose 4.5 days earlier than the time that the peak SCr level was achieved (31).…”
mentioning
confidence: 99%
“…Studies have demonstrated how, in preclinical models, changes to chromatin environment or microRNAs, such as miR181a and miR34a, may be indicative of proximal and distal tubular injury, how vanin-1 at the mRNA and protein level is an indicator of proximal tubular injury, how robust mRNA signatures measured in biofluids have the potential to be better predictors of region specific kidney injury, or how urinary proteomic biomarkers may serve as a valuable tool to investigate potential new drug candidates for the risk of renal safety (Bhatt et al 2010;Zhu et al 2012;Hosohata et al 2011;Kondo et al 2012;Rouse et al 2012). In recent years, exploratory approaches have focused on untargeted and targeted mass spectrometry-based proteomics and metabolomics but have also built on the expansion of genomics and epigenomics approaches.…”
Section: Novel Exploratory Biomarkersmentioning
confidence: 99%